Surgical treatment of haemorrhoidal disease – the current situation in Poland - Dziki, Lukasz; Mik, Michal; Trzcinski, Radzislaw; Buczynski, Jaroslaw; Kreisel, Anna; Skoneczny, Mariusz; Dziki, Adam (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : In cases of haemorrhoidal disease resistant to conservative treatment, surgical treatment is necessary to relieve the symptoms. Aim : To investigate the current methods used by Polish surgeons. Material and methods: Surveys were distributed to members of the Association of Polish Surgeons (APS), in which participants were asked a number of closed-ended questions regarding haemorrhoidal disease and the way they treated suffering patients Results : Out of the 1523 members of APS who received questionnaires, responses were received from 807 (52.9%) members. The Milligan-Morgan technique was indicated by 72.5% of surgeons as a leading surgical treatment, followed by Ligasure (15.5%), Ferguson (3.5%), DGHL (3.5%), other methods (3.5%), Parks (1.7%), and Longo (0%). The majority of participants (93%) indicated from 0 to 1 life threatening complications, 5% – from 2 to 3, and 2% > 4. A total of 83% of participants use a single dose of antibiotics prior to surgery. Conclusions : The Milligan-Morgan technique is the preferred method. The majority of procedures are performed in regional hospitals and university departments, and less commonly in private practices. The vast majority of surgeons in Poland are not convinced about the stapler technique, justifying this fact with the possibility of developing serious complications